Dynamics and Scaling of Explosion Cratering in Granular Media - Gordillo-Zavaleta, L (John Wiley and Sons Inc., 2018)
Granular cratering is a ubiquitous phenomenon occurring in various natural and industrial contexts. Although impact-induced granular cratering has been extensively studied, fewer experiments have been conducted on granular cratering via low-energy explosions. Here, we study the dynamics and scaling of explosion granular cratering by injecting short pulses of pressurized air in quasi-two-dimensional granular media. Through an analysis of the dynamics of explosion processes at different explosion pressures, explosion durations, and burial depths, we identify two regimes, the bubbling and the eruption regimes, in explosion granular cratering. Our experiments explore the distinctive dynamics and crater morphologies of these regimes and show the energy scaling of the size of explosion craters. We compare high-energy and low-energy explosion cratering as well as explosion and impact cratering in terms of their energy scalings. Our work illustrates complex granular flows in explosion cratering and provides new insights into the general scaling of granular cratering processes. © 2017 American Institute of Chemical Engineers AIChE J, 64: 2972–2981, 2018. © 2017 American Institute of Chemical Engineers